The strategies of travel agencies in Singapore - Nai, Yunni (2008)
Our research aims: (1)To evaluate the strategies of travel agents in Singapore., (2)To ascertain the Key Success Factors of travel agents, (3)To examine current industry trends and issues, and to explore appropriate strategies for travel agents.